MTV Brasil: o mercado comercial da música jovem - Oliveira, Ana Paola de (Universidade do Vale do Rio dos Sinos, 2004)
This study is about the process that cultural production goes through in order to turn itself public within a global context in the beginning of the XXI century. It matches the configurations of an oligopolist market that keeps its organization three merger and concentrations. It rascues the link the music will bring up with the brazilian television to put it, at last, within history and development of MTV Brazil. Also it presents the strategics points of commercing musical products analyzing the MTV programming. At the same time, it contextualizes the brazilian musical scenary from the industrial to alternative way in the technological development. Achieving then a study of case to the Political Economy Communication. This work here goes further of an analysis of the musical MTV Brazil contents, and a structured bibliographyc revision proceeding interviews into an analysis (within possible others) of he national music scenary. The research, finishing, means an openned channel to those who wish to discover the complexed and implicated intricate world which permeates the mass media and its interfaces, the scenary where that happens and how some famous names, songs, CDs, DVDs and many other products reach the top of the market.
Keywords: MTV Brasil; Comunicação de massa; Televisão; Programas musicais; ACCNPQ::Ciências Sociais Aplicadas::Comunicação